Leading Developmental Peer Observation of Teaching in Higher Education: Perspectives from Australia and England. Issue 3 (3rd July 2018) - Wingrove, Dallas; Hammersley-Fletcher, Linda; Clarke, Angela; Chester, Andrea
ABSTRACT: Whilst peer observation of teaching is well established as a practice that can enhance teaching quality, the challenge to fully embed this practice in universities remains unresolved. This article analyses the perspectives of 18 university leaders (nine Australian and nine English) drawn from a range of school-based leaders to senior leaders of learning and teaching. Our study indicates that some of the challenges associated with leading such schemes can be mitigated through approaches to educational leadership that enact a respectful and collegiate ethos. This we suggest can support developmental academic engagement in peer observation for positive and lasting change.